The effectivity of banana leaf-filtered cloth face masks as an alternative protection during the pandemic - Mohamad Saifudin Hakim; Mumtihana Muchlis; Fitra Duhita; Rita Dian Pratiwi (International Journal of Public Health Science (IJPHS), 2022)
The main transmission route of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is through individual droplets of respiratory secretions. Accordingly, the most basic preventive measure is wearing a face mask. Since the issue of medical waste during the pandemic is concerning, developing face masks made of reusable and biodegradable materials is necessary. This study aimed to develop "do-it-yourself" face masks and test the effectiveness of banana leaf-filtered cloth face masks. The design development was conducted by a series of trials for making a mask pattern that can be applied to the cloth. Then, we performed bacterial filtration efficiency (BFE) and water resistance tests to investigate the effectiveness of banana leaf-filtered cloth-based face masks. The dimensions of the developed face mask are 20x18 cm, with a semi-duckbill model, consisting of three layers of washable cotton cloth and a pocket designed for the banana leaf filter. Among 34 leaf-filtered face masks, 61.8% showed water resistance abilities. Based on the BFE test, the leaf-filtered face masks contained significantly fewer bacteria (the average of 0.417x103 cfu/cm2) compared to the cloth face masks without additional leaf filter (30x103 cfu/cm2). Thus, banana leaf-filtered cloth face masks could be considered as alternative protection during the pandemic.